Reducing the “digital divide” to reap the “digital dividend”: spatial differences and convergence of the digital economy in cities of China - Han, Jing; Song, Yang; Chen, Jisheng (Frontiers in Sustainable Cities, 2024)
Bridging the “digital divide” to benefit from the “digital dividend” reflects the inclusive development of the digital economy, which affects the sustainable development of the overall economy and society. Based on the different spatial perspectives of certain regions, city clusters, and cities, this study presents the “digital divide” and “digital dividend” for the development of China's digital economy. A combined entropy method was used to measure the development of the digital economy in cities of China from 2011 to 2019. The Dagum Gini coefficient and its decomposition were used to explore the spatial differences of the digital economy and their sources, while the coefficient of variation and the spatial panel model were used to examine the convergence of the digital economy. Our findings suggest that the development level of the digital economy in Chinese cities has continuously improved. Second, the spatial differences of the digital economy in the four regions and nine city clusters of China that were investigated are decreasing, indicating that the “digital divide” is narrowing and presenting a significant “digital dividend.” The total differences were mainly owing to those between the regions (among the city clusters). Third, the development of the digital economy in the four regions and nine city clusters demonstrated characteristics of σ, β, and club convergences. Finally, the evolution path of the spatial differentiation of the digital economy in cities of China is presented, and the “digital dividend” also demonstrates different stage characteristics. This study analyzed the spatial differences in the digital economy of cities in China and clarified the convergence and influence mechanisms of its development at different spatial scales. The findings provide a basis for the evolution of spatial and temporal patterns of the digital economy of cities in China and presents policy implications for promoting the regionally coordinated and sustainable development of the digital economy. Suggestions from the national and regional levels are more necessary to further narrow the “digital divide,” create a “digital dividend,” and digital drives sustainable economic development.